2021
DOI: 10.3390/antibiotics10111383
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Diversity of Ciprofloxacin Nonsusceptibility and Its Relationship with Minimum Inhibitory Concentrations in Nontyphoidal Salmonella Clinical Isolates in Taiwan

Abstract: This study analyzed the genetic diversity of ciprofloxacin (CIP) nonsusceptibility and the relationship between two major mechanisms and minimum inhibitory concentrations (MICs) of CIP in nontyphoidal Salmonella (NTS). Chromosomal mutations in quinolone resistance-determining regions (QRDRs) and plasmid-mediated quinolone resistance (PMQR) genes were searched from ResFinder, ARG-ANNOT, and PubMed for designing the sequencing regions in gyrA, gyrB, parC, and parE, and the 13 polymerase chain reactions for PMQR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
4
3
0
Order By: Relevance
“…The CIP MIC of S. Typhimurium PY1 carrying this construct was 0.0312 μg/mL, i.e., only a 2-fold increase compared with that of the vector control, indicating that aac(6′)-Ib-cr itself did not actually confer intermediate resistance (MIC ≥ 0.5 μg/mL) to ciprofloxacin. Such a phenomenon has also been reported in previous studies ( 13 , 14 ). S. Typhimurium PY1 carrying pAAC-AB, pAAC-ABRp, and pAAC-ABRc exhibited CIP MICs of 0.0312, 0.25, and 0.0625 μg/mL respectively.…”
Section: Resultssupporting
confidence: 90%
“…The CIP MIC of S. Typhimurium PY1 carrying this construct was 0.0312 μg/mL, i.e., only a 2-fold increase compared with that of the vector control, indicating that aac(6′)-Ib-cr itself did not actually confer intermediate resistance (MIC ≥ 0.5 μg/mL) to ciprofloxacin. Such a phenomenon has also been reported in previous studies ( 13 , 14 ). S. Typhimurium PY1 carrying pAAC-AB, pAAC-ABRp, and pAAC-ABRc exhibited CIP MICs of 0.0312, 0.25, and 0.0625 μg/mL respectively.…”
Section: Resultssupporting
confidence: 90%
“…Moreover, mutation Thr57→Ser in ParC was the only substitution detected among 47 tested Salmonella strains with ciprofloxacin MIC range 0.125–0.25 mg/L in S. Hadar , (0.19–0.75 mg/L) in S. Newport and (0.25–3 mg/L) in S. Infantis , respectively. This is in line with the reports of other authors that found Thr57Ser as the most prevalent mutation in ParC in NTS human isolates [ 14 , 24 , 25 ]. In accordance with a recent study, the ParC mutation at Thr57→Ser was detected as the main substitution in Salmonella enterica isolates from food-producing animals in China with a broad range of the ciprofloxacin MIC value (0.008–64 mg/L) [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, since the late 1990s, three types of plasmid-mediated quinolone resistance (PMQR) mechanisms have been identified: Qnr, which protects target enzymes; AAC(6’)-Ib-cr, which mediates the acetylation of certain quinolones; QepA and OqxAB, which produce mobile efflux pumps [ 13 ]. Although PMQRs alone are considered factors that can provide only a low level of resistance, their presence may aid bacteria to survive under low FQ pressure sufficiently to develop mutations in the DNA gyrase and/or topoisomerase IV genes, and to acquire high-level resistance to FQs [ 14 ]. These molecular mechanisms can be accumulative and together influence the observed FQ minimum inhibitory concentration (MIC) value.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the data (Hopkins et al, 2005 ; Zhan et al, 2019 ), mutations in chromosome and plasmid-mediated resistance genes all contributed to quinolones resistance, which is commonly used quinolones for Salmonellosis . Similar to a previous report in Taiwan (Fang et al, 2021 ), mutations in parC and gyrA were more likely to cause the resistance of quinolones.…”
Section: Discussionsupporting
confidence: 88%